2020
DOI: 10.3390/ijns6030072
|View full text |Cite
|
Sign up to set email alerts
|

Current Practices for U.S. Newborn Screening of Pompe Disease and MPSI

Abstract: Two lysosomal storage disorders (LSDs), Pompe disease and Mucopolysaccharidosis type I (MPSI) were added to the Recommended Uniform Screening Panel (RUSP) for newborn screening (NBS) in 2015 and 2016, respectively. These conditions are being screened with variable practice in terms of primary and reflex analytes (either biochemical or molecular testing) as well as collection of short- and long-term follow-up elements. The goal of this study is to evaluate practices of state health departments in regards to scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Thus, advocacy for the addition of newborn screening for MPS led to the addition of MPS I by the Advisory Committee on Heritable Disorders in Newborns and Children (ACHDNC) to the Recommended Uniform Screening Panel (RUSP) in February of 2016 [ 10 , 11 ]. Missouri was the first state to screen for MPS I [ 12 ], followed by several other states, and the state of Illinois has also started the screening of MPS II in 2017 [ 13 , 14 , 15 ], followed by Missouri in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, advocacy for the addition of newborn screening for MPS led to the addition of MPS I by the Advisory Committee on Heritable Disorders in Newborns and Children (ACHDNC) to the Recommended Uniform Screening Panel (RUSP) in February of 2016 [ 10 , 11 ]. Missouri was the first state to screen for MPS I [ 12 ], followed by several other states, and the state of Illinois has also started the screening of MPS II in 2017 [ 13 , 14 , 15 ], followed by Missouri in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical genetics testing by analysis of glycosaminoglycans (GAGs) in DBS [ 23 ] is primarily utilized to detect severe MPS I (Hurler syndrome), which is the main target of NBS, and may be sufficiently sensitive to detect at least some cases of attenuated MPS I [ 24 ]. Molecular testing, performed either as a 2TT or after case referral for follow-up testing, appears to be the preferred option in the United States for short-term follow-up of presumptive positives, regardless of the platform used for LSD enzyme testing [ 25 ].…”
Section: Prospective Screening Results From States Using Dmfmentioning
confidence: 99%
“…We additionally found that states with a larger Native American population screen for a significantly lower number of Lysosomal storage disorders. This is a notable finding because Lysosomal storage disorders, such as Pompe disease and Mucopolysaccharidosis type I, which were recently added to the RUSP, are screened for by two methods, “mass spectrometry (MS/MS) and digital microfluidics fluorimetry (DMF-F),” with MS/MS providing better precision ( 20 , 21 ). Lysosomal storage disorders are generally screened for by analyzing enzymatic activity from the dried blood spots collected for the NBS, but this method frequently returns high false positives, which require follow-up testing and care required to achieve accurate results ( 20 ).…”
Section: Discussionmentioning
confidence: 99%